30% Enhancement of Efficiency in Layered 2D Perovskites Absorbers by Employing Homo‐Tandem Structures. Issue 6 (2nd April 2019) - Chen, Yihua; Tan, Shunquan; Zhou, Ning; Yang, Ning; Zhou, Wentao; Wu, Yiliang; Weber, Klaus; Chen, Qi; Zhou, Huanping
Abstract : Layered two dimensional (layered 2D) organic–inorganic metal halide perovskites have attracted tremendous interest in photovoltaics due to its acceptable materials stability, especially the moisture resistance, when compared with their three dimensional counterparts. However, the limited carrier transport capability, which originates from the insulativity of bulky organic molecules, has significantly affected the resultant device efficiency. To create a shorter carrier pathway with sufficient optical density, the homo‐tandem device structure by using layered 2D perovskite absorbers is proposed. Following this strategy, the semi‐transparent device and filter bottom cells have been investigated and optimized using the same layered 2D perovskite absorber (BA2 MA3 Pb4 I13 ). The corresponding four‐terminal tandem device is successfully demonstrated with the champion power conversion efficiency of 14.42%, which is 30% higher than that of single BA2 MA3 Pb4 I13 perovskite devices (11.02%). A stabilized efficiency of 13.57% in the optimized champion tandem device also have been achieved. These results suggest alternatives to develop layered 2D perovskite based solar cells and other optoelectronic devices. Abstract : Layered 2D perovskite solar cells often suffer from poor carrier transport. Herein, the authors propose a homo‐tandem structure to extract the photogenerated carriers efficiently while retaining the optical density of the absorbers. It thus improves the power conversion efficiency of resultant devices by 30% without the penalty of moisture stability.